Synergistic strengthening behavior and microstructural optimization of hybrid reinforced titanium matrix composites during thermomechanical processing - Li,S; Han,Y; Shi,Z; Huang,G; Zong,N; Le,J; Qiu,P; Lu,W (Materials Characterization, 2020)
In this study, titanium matrix composites (TMCs) reinforced with hybrid TiB, TiC and RexOy (rare earth oxides) were successfully fabricated by vacuum arc melting technique. Subsequently thermomechanical processing was carried out to optimize the microstructure and investigate the synergistic strengthening behavior. It is found that the optimized microstructure mainly contained two typical regions: Region 1, reinforcement-lean region with coarse lamellar grains. Region 2, reinforcement-rich region containing fine equiaxed α grains comparing with reinforcement-lean region, all hybrid reinforcements distributed homogeneously at their grain boundaries and TiB fibers are perpendicular to the forging direction. It is shown that the reinforcement can stimulate the dynamic/static recrystallization during the thermomechanical processing. The tensile strength was significantly enhanced by the ternary reinforcements and the thermomechanical processing. A well-matched relationship between microstructure and mechanical properties is obtained. When the reinforcement content is 2.5vol%, the tensile strength at room temperature and high temperature (700°C) increased to 1214MPa and 552MPa, while the TMCs maintained a good elongation of 5.1% and 58% respectively. The strengthening mechanism could be attributed to the refinement of the matrix grain, the solid solution strengthening of C element and the load-bearing capability of TiB and ternary oxide clusters.